Contextual bureaucratic reform towards golden Indonesia 2045: Enhancing adaptive capacity in the VUCA era - Bonataon Maruli Timothy Vincent Simandjorang (Privietlab, 2026)
Indonesia’s Bureaucratic reform or Reformasi Birokrasi (RB) must move beyond administrative compliance and index-based achievement toward a contextual model capable of responding to Volatility, Uncertainty, Complexity, and Ambiguity (VUCA). This study examines the adaptive capacity of government institutions and formulates policy directions to support the Grand Design of National Bureaucratic Reform 2025–2045 and Vision of Golden Indonesia 2045. The policy paper applies the Adaptive Capacity Wheel developed by Gupta et al. (2008), covering six dimensions and 22 criteria, within a sequential exploratory mixed-method design. Data were collected in April 2026 through interviews, observations, document analysis, expert judgement, and stakeholder assessment involving experts and stakeholders across the Ministry of National Development Planning or Badan Perencanaan Pembangunan Nasional (Bappenas), the Province of West Nusa Tenggara or Nusa Tenggara Barat (NTB), and the Regency of Bima. The results show different levels of institutional readiness in the three countries. Bappenas achieved an adaptive capacity score of 1.17, indicating a positive institutional effect supported by strong leadership, diverse perspectives, and fair governance. The NTB scored 0.79, classified as slightly positive, with strengths in learning capacity and accountability but limitations in operational flexibility, cross-sector coordination, and resource allocation. Bima scored 0.29, which is also slightly positive, reflecting basic institutional foundations but weaknesses in leadership, resources, and policy experimentation. The findings demonstrate that improvements in the RB Index do not automatically translate into strong adaptive capacity. Therefore, RB should adopt differentiated strategies, institutionalize organizational learning, strengthen cross-agency delivery mechanisms, integrate evidence and digital governance, and link reform performance to measurable public and development outcomes.